"I don't know": a usage-based approach to familiar collocations in non-fluent aphasia. Issue 2 (1st February 2019) - Bruns, Claudia; Varley, Rosemary; Zimmerer, Vitor C.; Carragher, Marcella; Brekelmans, Gwen; Beeke, Suzanne
ABSTRACT: Background : Familiar collocations (e.g., "it's alright") are an important part of everyday conversation. Such word combinations are often retained in speakers with Broca's aphasia. However, only few investigations have studied the forms and functions of familiar collocations available to speakers with Broca's aphasia. Aims : We first apply a frequency-based perspective to word combinations produced by speakers with Broca's aphasia and their conversation partners (CPs), and compare the frequency characteristics of word combinations in dyadic and non-dyadic speech. Second, we investigate the conversational functions of one prominent familiar collocation, "I don't know" (IDK). Methods & Procedures : In the first analysis, speech samples from interactions of nine dyads (each a speaker with Broca's aphasia and their CP) were examined. Non-dyadic samples were selected from 39 speakers with Broca's aphasia from AphasiaBank (MacWhinney et al., 2011). The Frequency in Language Analysis Tool (FLAT; Zimmerer & Wibrow, 2015) was used to estimate collocation strength (the degree of association between words in a combination) of well-formed bigrams (two-word combinations) and trigrams (three-word combinations). The second analysis presents a qualitative investigation of uses of IDK in dyadic exchanges. Outcomes & Results : Analysis 1 revealed that residual trigrams in Broca's aphasia were more strongly collocated in comparison to language produced by CPs. There was no difference in frequency-based profiles between dyadic and non-dyadic aphasic speech. Analysis 2 indicated that speakers with Broca's aphasia and CPs used IDK to achieve a variety of communicative functions. However, patterns specific to each participant group were found. Conclusions : These findings highlight that frequency-based analysis is useful in explaining residual, grammatically well-formed word combinations in Broca's aphasia. This study provides evidence that IDK can aid turn construction in aphasia.